Secret Image Sharing Based on Discrete Cosine Transform - Hashim, Ashwaq T.; E. George, Dr. Loay (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
The main challenges facing secure image sharing tasks are the increase of sharing volume and sharing-control flexibility. A new scheme based on DCT is developed to perform packet secret image sharing, the DCT is used to reduce the secret image size firstly, then it employs the (k, n) threshold sharing scheme to generate the shadow images. The main signal decomposition attribute of the transform is utilized to divide the secret image into uncorrelated shares. Expermintal results are given to illustrate the characteristic of this methods.